Innovative Pedagogical Activity: Content and Structure - Alisherovich, Tashpulatov Farhad; Toshboyeva, M. B. (European Journal of Life Safety and Stability (2660-9630), 2021)
This article proposes to use innovative approaches in the activities of higher education. In order to ensure the competitiveness of graduates of higher educational institutions, the issue of introducing innovations into higher education was considered in order to form the innovative potential of future specialists in the process of professional development of the strategic development of Uzbekistan in the conditions of modern civilization.